Pengembangan Keterampilan Kewirausaahaan pada Pelaku Usaha Desa Pasirtanjung, Kecamatan Tanjungsari, Kabupaten Bogor - R.A. Fadhallah; Yudhaningrum, Lupi; Erik; R.Damanik, Novitasari (Jendela Akademika, 2023)
Economical problem is the root of other problems such as social, culture and human resource. Hence, it needs to be solved in nation building plan. Village of Pasirtanjung, in district of Tanjungsari Bogor, West Java has prioritized human resource enhancement through even distrubution of Education and improvement in civil economic growth. There are some solutions to address this economical problem and to improve civil economic growth. One of the solutions is to empower the society to become entrepreneur or business person. To be an entrepreneur or business person does not take a money capital only. Beside money capital, it takes an entrepreneur skill so individual be able to run the business successfully and profitable. As our community service program, Village of Pasirtanjung, in district of Tanjungsari Bogor, West Java, has some potencies to enhance entrepreneur skills. Hence, this community service program focuses on the enhancement of entrepreneur skill of business person, as a solution to enhance human resource capacity and improve civil economic growth. The outcome of this community service is evidence of entrepreneur skill improvement, activity video, and cooperation agreement.